2013
DOI: 10.1080/21622515.2013.770558
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of glycerol, monoglycerides and diglycerides present in biodiesel produced from soybean oil

Abstract: The most common methods currently used for the removal of waste glycerol, monoglycerides and diglycerides remaining after phase separation during biodiesel production involve wet processes. These procedures are not environmentally viable because they require large volumes of water and thus generate significant quantities of effluent. In this study, adsorption was employed to replace this purification step. Some commercial activated carbons were tested along with adsorbents chemically modified with HNO3. A kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…As there is no literature supporting the purification of WVO specifically for the production of epoxy resins, different purification procedures were tested based on existing methodologies reported for the biodiesel area. [26,27] These procedures target the removal of highly oxidized compounds formed by the frying process (e.g. aldehydes) and hydrolysis products such as mono-and diglycerides.…”
Section: Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…As there is no literature supporting the purification of WVO specifically for the production of epoxy resins, different purification procedures were tested based on existing methodologies reported for the biodiesel area. [26,27] These procedures target the removal of highly oxidized compounds formed by the frying process (e.g. aldehydes) and hydrolysis products such as mono-and diglycerides.…”
Section: Purificationmentioning
confidence: 99%
“…aldehydes) and hydrolysis products such as mono-and diglycerides. Samples were purified by extraction of polar products with water at 60 C (single and multiple extraction) and adsorption with activated carbon and chemically modified activated carbon with nitric ions as described by Vásques et al [27] This permitted the classification of the oil samples in three different categories: ppm are specifically associated with n-alkanals, (E)-2-alkenals and (E,E)-2,4-alkadienals. [31,32] Investigation of spectra of samples after performing the purification methods demonstrated that all methods were efficient to remove highly oxidized compounds as signals at the 9 -10 ppm region were eliminated.…”
Section: Purificationmentioning
confidence: 99%
“…WVO was purified by single 117 and multiple extractions and subsequently purified with activated carbon. 118 Moreover, Issam et al reported on the study of properties of blending various ratios of palm oil-based alkyd to epoxy resins. 113 In general, alkyd resin and epoxy resin showed good compatibility.…”
Section: Polyepoxidesmentioning
confidence: 99%